Analisis Kendala Perizinan Radio Kijang Kencana (K2) FM sebagai Lembaga Penyiaran Publik Lokal Indramayu dalam Perspektif Peran Pemerintah Kabupaten Indramayu - Sjuchro, Dian Wardiana; Rusmana, Agus; Sjafirah, Nuryah Asri; Viannisa, Nadhifa; Santoso, Budi (Jurnal Publisitas, 2024)
The business climate in the publishing sector has become quite a complex issue in Indonesia. But not only that, in publishing, licensing has its own dynamics. Media ownership must go through a licensing process which can be said to be easier than before. But in reality, there are still many Delivery Institutions that experience licensing problems, one of which is K2 FM Radio as a Local Public Delivery Institution (LPPL) in Indramayu Regency. In this research, the researcher wants to analyze what are the obstacles for K2 FM Radio, starting from its status which must comply with the law to the permit which has not been extended since 2022 and the researcher wants to know the government's role in the obstacles facing K2 FM Radio's licensing. This research uses a qualitative research method with a case study approach. Data collection techniques were carried out through interviews with 10 informants in the form of Focus Group Discussion (FGD), documentation studies and literature studies. The results of this research are that the obstacle to K2 FM Radio licensing is the dynamic change in position holders so that there is no official role that can focus on handling K2 FM Radio licensing issues. Apart from that, the government's role is minimal so that the budget support issued by K2 FM Radio as LPPL is not granted. K2 FM Radio needs someone who really loves radio so that the radio can develop.